Evaluation of the relationship between the body positioning and the postural comfort of non-professional cyclists: a new approach - Baino, F. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: Most biomechanical studies on bicycle ergonomics focused on racing efficiency and often neglected the investigation of cycling comfort, due to the difficulties related to the people`s subjective feelings. This research work aims at analyzing the comfort on bicycle from an objective viewpoint; specifically, an attempt to relate subject`s preferences, determined in a dynamic way, with his/her physical features, acquired by means of anthropometric measurements, was carried out. The validity of some existing and commonly used "rules of thumb" for bicycle fitting is discussed and investigated, and new indications are also proposed to achieve an optimal bike configuration. METHODS: A group of 120 volunteers was considered in this study; they were non-professional cyclists. First, the participants` anthropometric features were acquired; afterwards, the volunteers were asked to cycle on a bicycle fitting system (adjustable gym bike) and then to modify the simulator settings till the optimal subjective feelings of comfort are reached. The linear correlation coefficient between the measured anthropometric features and the geometrical preferences adopted on the cycling simulator was calculated. RESULTS: On one hand, the data analysis allows to propose new indications to achieve an optimal postural comfort on the basis of the physical features of the subject, but, on the other hand, the results confirm that the comfort on bicycles is highly related to personal preferences and, therefore, it is strongly subjective. CONCLUSION: The main conclusions and implications of this study can be summarized as follows: 1) the comfort on bicycle is strongly subjective as it is highly related to personal preferences; 2) an optimal bicycle setting can be achieved only by taking in to account the most relevant anthropometric features of every single cyclist; 3) a station for acquiring cyclists` anthropometric measurements and a bicycle simulator (adjustable gym bike) can act as very useful tools for designing optimal and custom-made bicycle configurations.